Dinamika Kepemimpinan Birokrasi untuk Efektivitas Pelayanan pada RSUD Er Dabi Kabupaten Yalimo - Alimuddin, Unding; Muhdiarta, Untung (JURNAL EKOLOGI BIROKRASI, 2025)
This study aims to analyze the influence of local bureaucratic leadership on the effectiveness of health services at Er Dabi Regional Hospital in Yalimo Regency and to identify supporting and inhibiting factors for health services in this remote area, including the implications of regional health decentralization policies. The urgency of this research is to improve the quality of health services in Yalimo, which remain constrained by bureaucracy, medical staff, and infrastructure. Using a qualitative case study design approach, data were collected through in-depth interviews with health bureaucratic officials, hospital leaders, medical personnel, and patients and their families; participant observation at Er Dabi Regional Hospital; and analysis of health policy documents and hospital performance reports. Informants were selected using purposive sampling to ensure a diversity of perspectives, and data were analyzed thematically to uncover patterns, themes, and relationships between factors. The results indicate that the formal bureaucratic structure remains rigid and hierarchical, hindering adaptive decision-making and responsive resource distribution; transformational leadership styles are suboptimal due to a lack of intensive training, resulting in often-resistance-based initiatives; cross-sector coordination and good governance principles such as transparency, accountability, and public participation are also inadequate; and limited medical personnel, diagnostic facilities, and infrastructure create bottlenecks in the service process, resulting in low patient satisfaction and delayed treatment. The conclusion states the need for a transformation toward a participatory and innovative leadership model supported by a hybrid bureaucratic structure that combines operational flexibility and local cultural inclusion. Recommendations include implementing an adaptive managerial capacity building program, transformational leadership workshops, digitizing services through SIMRS and telemedicine, strengthening collaborative governance through cross-sector forums and public-private partnerships, and implementing a real-time monitoring system for drug procurement and ongoing performance evaluation to improve access, quality, and sustainability of health services in Yalimo Regency.